Mental health trends among medical students. Issue 3 (4th May 2023) - Nair, Muktha; Moss, Nathaniel; Bashir, Amna; Garate, David; Thomas, Devon; Fu, Shangyi; Phu, Daniel; Pham, Christine
Abstract: Student mental health concerns can manifest in several forms. Medical students juggling a multitude of trials (i.e., intense academic rigor, financial debt, sleep deprivation, lack of control, continual exposure to sickness and death, and training mistreatment) can help explain the higher prevalence of psychological disorders within this population. Furthermore, these mental health difficulties are not static; certain challenges move into the forefront as students face key transition points in schooling. Primary examples include the entry year of medical school, the shift from preclinical curriculum to clinical training, and the final moments prior to beginning residency. Given the existing mental health trends among medical students at baseline, it can be concluded that the COVID-19 pandemic has exacerbated the stress, anxiety, and depression associated with medical education. Solutions do indeed exist to address the moral injury medical students face, from expanded crisis management training and implementation of peer support networks to destigmatization of and improved access to professional mental health resources. It is up to the curators of the medical education system to make these solutions the new status quo.